One or many? Multi-species livestock grazing influences soil microbiome community structure and antibiotic resistance potential - Mhuireach, Gwynne Á.; Dietz, Leslie; Gillett, Thomas (Frontiers in Sustainable Food Systems, 2022)
Soil health has been highlighted as a key dimension of regenerative agriculture, given its critical importance for food production, carbon sequestration, water filtration, and nutrient cycling. Microorganisms are critical components of soil health, as they are responsible for mediating 90% of soil functions. Multi-species rotational grazing (MSRG) is a promising strategy for maintaining and improving soil health, yet the potential effects of MSRG on soil microbiomes are poorly understood. To address this knowledge gap, we collected soil microbial samples at three timepoints during the 2020 grazing season for 12 total paddocks, which were equally split into four different grazing treatments—cattle only, sheep only, swine only, or multi-species. Shallow shotgun metagenomic sequencing was used to characterize soil microbial community taxonomy and antibiotic resistome. Results demonstrated broad microbial diversity in all paddock soil microbiomes. Samples collected early in the season tended to have greater archaeal and bacterial alpha diversity than samples collected later for all grazing treatments, while no effect was observed for fungi or viruses. Beta diversity, however, was strongly influenced by both grazing treatment and month for all microbial kingdoms, suggesting a pronounced effect of different livestock on microbial composition. Cattle-only and swine-only paddocks were more dissimilar from multi-species paddocks than those grazed by sheep. We identified a large number of differentially abundant taxa driving community dissimilarities, including Methanosarcina spp., Candidatus Nitrocosmicus oleophilus, Streptomyces spp., Pyricularia spp., Fusarium spp., and Tunggulvirus Pseudomonas virus ϕ-2. In addition, a wide variety of antibiotic resistance genes (ARGs) were present in all samples, regardless of grazing treatment; the majority of these encoded efflux pumps and antibiotic modification enzymes (e.g., transferases). This novel study demonstrates that grazing different species of livestock, either separately or together, can impact soil microbial community structure and antibiotic resistance capacity, though further research is needed to fully characterize these impacts. Increasing the knowledge base about soil microbial community structure and function under real-world grazing conditions will help to construct metrics that can be incorporated into traditional soil health tests and allow producers to manage livestock operations for optimal soil microbiomes.